Pelatihan Simulasi Debat Berbahasa Inggris Berbasis Vlog Terhadap Mahasiswa Universitas Harapan Medan - Kristiana, Vera; Yuliana, Yayuk; Dewi, Ratna Sari; Ningsih, Ayu Melati; Tarihoran, Rezky Khoirina (LPPI UMN AL WASHLIYAH, 2024)
This training was held at Universitas Harapan Medan which is located at Jl. Imam Bonjol No. 35 Medan. Based on the results of observations carried out by the service team, several problems faced by students at the university were obtained, especially those related to English. Most of them still don't dare to communicate in English and are still passive when there are activities or competitions held by the campus, such as English debate competitions. English language experts consider English Debate to be very effective when applied to improve speaking. It is hoped that students will be more enthusiastic about participating in English debate training if it is combined with video blog (vlog) media. Video media is a type of audio-visual media. This media can increase students' interest in learning because students can listen and see pictures. Service activities are carried out in three stages. The first stage is the preparation stage. In this stage, the service team carries out a preliminary survey to see the conditions in partners and also look for problems faced by students, especially in terms of English. The next stage is the stage of implementing community service activities. The final stage is the evaluation stage. In this stage, evaluation is carried out on the results achieved by the training participants. Further input and improvements can be made at this stage. Evaluation is provided by collecting data obtained from training activities.